Organizational Justice: Yesterday, Today, and Tomorrow - Greenberg, Jerald (Journal of Management, 1990)
The present article chronicles the history of the field of organizational justice, identifies current themes, and recommends new directions for the future. A historical overview of the field focuses on research and theory in the distributive justice tradition (e.g., equity theory) as well as the burgeoning topic of procedural justice. This forms the foundation for the discussion offive popular themes in contemporary organizational justice research: (a) attempts to distinguish procedural justice and distributive justice empirically, (b) the development of new conceptual advances, (c) consideration of the interpersonal determinants of procedural justice judgments, (d) new directions in tests of equity theory, and (e) applications of justice-based explanations to many different organizational phenomena. In closing, a plea is made for future work that improves procedural justice research methodologically (with respect to scope, setting, and scaling), and that attempts to integrate and unify disparate concepts in the distributive and procedural justice traditions.